Status of northern mountain caribou (Rangifer tarandus caribou) in Yukon, Canada - Hegel, Troy M.; Russell, Kyle (Rangifer, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false SV X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Normal tabell"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-fareast-language:EN-US;} --> <!--[endif] -->Caribou (Rangifer tarandus) are an important ecological, cultural and economic resource in Yukon, Canada. Three caribou ecotypes occur within Yukon: Grant’s (R. t. granti), northern mountain (R. t. caribou), and boreal (R. t. caribou). Northern mountain caribou are classified as a species of special concern under Canada’s Species at Risk Act, and a national management plan for northern mountain caribou was recently completed. Twenty-six northern mountain caribou herds occur at least partially within Yukon, representing approximately 30,000 – 35,000 animals. Active monitoring of Yukon’s northern mountain caribou began in earnest in the early 1980s. To date, over 200 fall composition surveys have been carried out, over 1000 animals have been fitted with radio-collars, and nearly 40 formal population estimates have been completed. Disease and contaminant monitoring of these caribou has indicated relatively low disease prevalence and contaminant loading. Northern mountain caribou are harvested in Yukon, with an average of 230 caribou harvested per year by licensed hunters (1995 – 2012) and an unknown number by First Nation hunters. Future challenges related to caribou management and conservation in Yukon include increasing levels of industrial development primarily through mineral exploration and development, ensuring harvest of these herds is conducted sustainably given the absence of total harvest information, inter-jurisdictional management of shared herds, existing uncertainty surrounding herd distribution and delineation, and dealing with vehicle-related mortality of caribou for certain herds. Overall, the population status (i.e., trend) of eight herds is known, with two increasing, two decreasing, and four stable.